How intellectual capital, knowledge management, and the business environment affect thailand’s food industry innovation - Yaklai, Pimsara; Suwunnamek, Opal; Srinuan, Chalita (My University, 2018)
In 2015, Thailand employed nearly 11% of the population in agriculture, which has always been a stable and prosperous component of the economy. Having a rich natural abundance of resources, combined with significant investments in technology, food safety, and research and development (R&D) have helped contribute to Thailand being labeled as “Kitchen of the World.” Given these priorities, stratified sampling was employed to select 246 individuals from the target population. Confirmatory factor analysis was used, followed by a structural equation model to analyze how intellectual capital, knowledge management, and the business environment affect innovation in Thailand’s entrepreneurial food industry. The research survey was conducted using a questionnaire which contained a 7-level Likert type agreement scale. Results from the study revealed that the food industry’s knowledge management capability was the most important factor (0.60), which was also influenced directly by the organization’s intellectual capital (0.44). Of lesser importance was intellectual capital (0.39) and the business environment (0.39).
Keywords: Agriculture; CFA; Food Innopolis Project; SEM; Thailand 4.0